A Novel Ultrathin SiO Layer Endowing Significant Improvement of Interface Properties for Nickel‐Rich Cathode Materials in Lithium‐Ion Batteries. Issue 7 (10th May 2020) - Dai, Hui; Cao, Haishang; Du, Fanghui; Zhou, Qun; Adkins, Jason; Sun, Pengpeng; Hu, Die; Zheng, Junwei
Abstract : A molecular coating strategy is used to modify the surface of LiNi0.8 Co0.1 Mn0.1 O2 with a monolayer, or a few layers, of [3‐(trimethoxysilyl)propyl]urea. Upon calcination of the material, an ultrathin SiO layer is formed on the surface of LiNi0.8 Co0.1 Mn0.1 O2 . The modification of the ultrathin SiO layer results only in a slight decrease in the specific capacity of LiNi0.8 Co0.1 Mn0.1 O2 (≈204 mAh g −1 at 0.1 C), however, the ultrathin SiO layer endows the material with excellent cycling stability and rate capability. The electrode with surface‐modified material can deliver 87.5% of the initial discharge capacity after 300 cycles at 1 C, whereas the corresponding capacity retention of the pristine counterpart is only 62.5%. Similarly, the capacity retentions for the modified material and pristine counterpart are 76.0% and 55.7% at 2 C, respectively, relative to the capacities at 0.1 C. The results are ascribed to the covalently bonded structure of the SiO layer efficiently alleviating the side reaction of the electrolytes and enhancing the kinetics of the charge transfer processes at the interface. This strategy would be also applicable to other metal oxide materials to optimize the performance for lithium‐ion batteries. Abstract : A novel ultrathin SiO layer is generated by molecular coating strategy to modify the surface of LiNi0.8 Co0.1 Mn0.1 O2, leading to great improvement in cycling durability and rate capability due to efficient alleviation of the side reactions of the electrolyte and enhancement of the kinetics of the charge transfer at the interface.